Prevention of Fungal Contamination in Plant Tissue Culture Using Cyclic Lipopeptides Secreted by Bacillus amyloliquefaciens AB30a (Plant Tissue Culture and Biotechnology, 2019)
Plant tissue culture has revolutionized the field of plant biotechnology. However, there are certain obstacles which overall restrain the output of the plant tissue culturing. One of them is contamination of the tissue culture stock which is a major problem limiting the output. Aegle marmelos (L.) is a medicinal plant whose genotype qualities are maintained through clonal propagation of nodal segment as an explant. It harbors plethora of fungi which curbs the successful in vitro propagation. Chemical fungicide like bavistin is used to prevent the contamination in tissue culture which raises the environmental concerns. Thus, use of microbially derived antifungals can help in preventing fungal growth with benefit of positively impacting the plant growth. Here, authors investigated the use of heat stable lipopeptides which are secondary metabolites derived from Bacillus amyloliquefaciens AB30a for prevention of contamination in tissue culturing of nodal explants of A. marmelos positively impacting its in-vitro propagation.Plant Tissue Cult. & Biotech. 29(1): 111-119, 2019 (June)